2003
DOI: 10.1088/0268-1242/18/6/309
|View full text |Cite
|
Sign up to set email alerts
|

A study of deep levels in vanadium-doped GaAs grown by OMVPE

Abstract: Vanadium(V)-doped GaAs layers grown by metal organic vapour phase epitaxy using vanadium tetrachloride as a doping source were characterized by deep level transient spectroscopy. The only deep level detected in undoped GaAs is EL2. After V doping, the EL2 defect was not detected. This observation is explained by a reaction involving V and the EL2 arsenic antisite. V doping creates an electron trap (E1) at 0.14 eV below the conduction band, associated with the transition V 3+ /V 2+ , and a broad band (E2) of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…3). This is comparable to the variation of V incorporation GaAs, where a is about 1.9 [21]. The increase of the V background level along the growth direction indicated some reactor memory effect.…”
Section: Resultssupporting
confidence: 75%
“…3). This is comparable to the variation of V incorporation GaAs, where a is about 1.9 [21]. The increase of the V background level along the growth direction indicated some reactor memory effect.…”
Section: Resultssupporting
confidence: 75%
“…In Ref. [16], we have shown that V incorporates in Ga sites, which causes reduction in Ga vacancy density.…”
Section: Resultsmentioning
confidence: 94%
“…The growth procedure, electrical and optical properties of the grown layers are described in Refs. [13][14][15][16].…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 shows the room temperature Hall carrier concentration for samples which were as-grown and annealed at 750 • C. The data for the as-grown GaAs:V have already been published [17] but are reproduced here for the sake of completeness. The V where α is about 1.9 (figure 1 in [18]). After annealing at 750 • C, two domains are clearly observed.…”
Section: Hall Effect Measurementsmentioning
confidence: 99%
“…V doping creates an electron trap E1 at 0.14 eV below the conduction band, associated with the transition V 3+ /V 2+ . The DLTS spectra of the as-grown Vdoped layers are described in detail in [18]. After annealing we noted the appearance of the E3 trap.…”
Section: Pl Measurementsmentioning
confidence: 99%